Let a , b , c be the real roots of the cubic equation 2 t 3 + 3 t 2 − 9 t − 6 = 0 . Suppose that ∣ ∣ ∣ ∣ ( b − c a + c − a b + a − b c ) ( a b − c + b c − a + c a − b ) ∣ ∣ ∣ ∣ = n m for some relatively prime positive integers m and n . Find m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Before I give my solution, using Vieta's formula gives a + b + c = -3/2, ab + bc + ac = -9/2, and abc = 3.
Also the following identities are useful:
(a + b + c)^2 - 3(ab + bc + ac) = a^2 + b^2 + c^2 - ab - bc - ac = 63/4
a^3 + b^3 + c^3 = (a + b + c)(a^2 + b^2 + c^2 - ab - bc - ac) + 3abc = (-3/2)(63/4) + 9 = -117/8.
(a + b + c)^3 = a^3 + b^3 + c^3 + 6abc + 3ab^2 + 3ba^2 + 3ac^2 + 3ca^2 + 3bc^2 + 3cb^2 or -27/8 = -117/8 + 18 + 3ab^2 + 3ba^2 + 3ac^2 + 3ca^2 + 3bc^2 + 3cb^2 which implies ab^2 + ba^2 + ac^2 + ca^2 + bc^2 + cb^2 = -9/4.
Now, the attack here is to make both factors one term which makes the first factor equal to 27/8 and the second -1/3 (after cancelling the denominator on the first and its negative on the second). This gives m/n = |-9/8| = 9/8. Hence, 17.
Problem Loading...
Note Loading...
Set Loading...
first of all, lets review Newtons sum a + b + c = − 2 3 , a 2 + b 2 + c 2 = 4 4 5 , a 3 + b 3 + c 3 = − 8 1 1 7 , a b c = 3 now, simplify b − c a + c − a b + a − b c = − a c 2 − a 2 b + a 2 c − c b 2 + b c 2 + a b 2 a 2 c − a 2 b + a b 2 + b 2 c + c 2 b + a c 2 − a 3 − b 3 − c 3 − 3 a b c and c a − b + a b − c + b c − a = a b c b 2 c − b c 2 + a c 2 − a 2 c + a 2 b − a b 2 now notice that − a c 2 − a 2 b + a 2 c − c b 2 + b c 2 + a b 2 b 2 c − b c 2 + a c 2 − a 2 c + a 2 b − a b 2 = − 1 , so the expression now is − a b c a 2 c − a 2 b + a b 2 + b 2 c + c 2 b + a c 2 − a 3 − b 3 − c 3 − 3 a b c factorise − a b c a 2 ( b + c ) + c 2 ( a + b ) + b 2 ( c + a ) − ( a 3 + b 3 + c 3 ) − 3 a b c from the first line we can tell a + b = − 2 3 − c and so on, now substitute that to get − a b c a 2 ( − 2 3 − a ) + c 2 ( − 2 3 − c ) + b 2 ( − 2 3 − b ) − ( a 3 + b 3 + c 3 ) − 3 a b c simplify and factorise again to get − a b c − 2 3 ( a 2 + b 2 + c 2 ) − 2 ( a 3 + b 3 + c 3 ) − 3 a b c substitute the values by Newton's and we get the value is ∣ ∣ ∣ ∣ 8 − 9 ∣ ∣ ∣ ∣ and 9 + 8 = 1 7